Socio-environmental vulnerability and its connection with the urban space in the sector “El Negrital” - Loor Zamora, Anthony Enrique (2024)
This research aims to analyze the interrelation between urban space and the socio-environmental vulnerability of the “El Negrital” sector, Portoviejo, Manabí, Ecuador. Through a mixed methodological approach, which incorporated both bibliographic research and field research, a close connection was revealed between the quality of life of residents and deficiencies in the provision of basic services, road infrastructure and the shortage of green spaces. These shortcomings have generated a vulnerable urban environment, exposing the community to risks and limiting its opportunities. The results obtained show the urgency of a comprehensive intervention that seeks to reduce socio-spatial inequalities and strengthen the resilience of the sector. An action plan is proposed that promotes the creation of a more sustainable and equitable urban environment, through the improvement of infrastructure, the diversification of land uses and the generation of green spaces, in order to guarantee a better quality of life for the inhabitants of "El Negrital" and contribute to a more fair and balanced urban development.